Bead milling liberates the antioxidant properties of nanosized tubers of Vernonia guineensis Benth (Asteraceae) - Eya'ane Meva, Francois; Djomaha, Ludrice Dorence Yossa; Nasim, Muhammad Jawad; Ntoumba, Agnes Antoinette; Kouemegne, Armelle Michelle Houatchaing; Ottou, Patrice Brice Mvogo; Loe, Gisele Etame; Dibong, Siegfried Didier; Jacob, Claus (BIORE Scientia Publisher, 2024)
Vernonia guineensis Benth. (Asteraceae), locally known as ‘African ginseng’, is an herbaceous plant with various therapeutic properties, sold by herbalists, and used in several traditional African preparations. Nanosizing has the capability to potentiate those preparations in their pharmacological properties. Premilling and extensive grinding using a planetary ball mill were used to reduce the size of V. guineensis tubers towards antioxidant studies. Water was used as an environmental friendly, cost effective solvent and dispersant to generate a nanocolloidal suspension of V. guineensis tubers. Size and size distribution were determined via photon correlation spectroscopy at room temperature which allows discussion on stability by Zeta potential and polydispersity index. Phytochemical screening shows presence of alkaloids, coumarins, polyphenol, saponins, tanins, terpenes, and anthraquinones. The distribution curve in water shows a polydispersed system with large hydrodynamic particles of size close to 1000 nm and a Z-average of 484.5 nm. The preparation separate in two phases with polydispersity index 0.217 for the supernatant and 0.543 for the suspension. In the supernatant and suspension, the particles zeta potential were -12.3 mV and -13.7mV respectively. The Mastersizer analysis indicates that there are smaller particles in volume in the supernatant than in the suspension. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity shows an increase in antioxidant activity, compared to that of ascorbic acid, in the nanoformulated state. These findings allow us to conclude on the potential of size reduction when compared to solvent extraction in pharmacologic preparations.